Bubble pinch-off in Newtonian and non-Newtonian fluids. (12th October 2017) - Jiang, Xiao F.; Zhu, Chunying; Li, Huai Z.
Graphical abstract: Air bubble pinch-off sequences in 0.50% PAAm solution ( Q = 0.5 mL/min). Highlights: Air bubble pinch-off in Newtonian and non-Newtonian fluids was investigated. Scaling law exponent ranges from 0.5 to 1 in Newtonian fluids. Scaling law exponent is between 0.5 and 1 for lowly shear-thinning fluids. Non-universal scaling was observed in highly shear-thinning fluids. Experimental data were validated by the numerical simulation. Abstract: Bubble pinch-off is a rapid process and until now is not well-understood especially for the final stage near the breakup point. In this work, we aim at investigating the air bubble pinch-off at a submerged nozzle in various fluids, including Newtonian and non-Newtonian fluids. Different fluids exert different effects on the pinch-off dynamics as well as shape evolution immediately after pinch-off. A scaling law was applied to describe the bubble pinch-off in Newtonian fluids and the exponents: b = 0.5 for low viscosity fluids and b = 1 for high viscosity fluids, are in a good agreement with the conventional values predicted by the numerical simulation. For bubbles in non-Newtonian fluids, the pinch-off dynamics is mainly governed by the fluid rheology. The universal scaling exponent exists between 0.5 and 1 for low shear-thinning fluids while a non-universal character occurs for bubble pinch-off in high shear-thinning fluids. Our experimental results were confirmed by the numerical simulation.